MITOCHONDRIAL DNA DIVERSITY IN FOUR POPULATIONS OF INDONESIAN FRESHWATER GIANT PRAWN (Macrobrachium rosenbergii) - Ratu Siti Aliah (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Mitochondrial DNA has been widely applied to analyze fish genetic diversity, especially the cytochrome oxidase subunit I (COI) gene, which can be used as a marker of typical variation patterns, both intraspecific and interspecific crossbreeding. Haplotype diversity was observed in four populations of giant freshwater prawns (Macrobrachium rosenbergii) originating from Peureulak River in Aceh, Tabuk River in South Kalimantan, Bengawan Solo River in East Java, and the Siratu strain. Haplotype diversity was observed in the mitochondrial DNA COI gene of 1516 bp and restricted using 5 enzymes, namely AvaII, MspI, RsaI, HaeIII, and TaqI. The diversity of mtDNA COI haplotypes in the population of Peureulak River, Tabuk River, Bengawan Solo River, and Siratu were 0.8183, 0.6222, 0.7461, and 0.8044, respectively. The dendrogram of genetic distance showed that the Bengawan Solo River populations and the Siratu strain were in the same cluster, while Peureulak River and Tabuk River populations were in another group. The four populations can be used as genetic sources in crossbreeding activities based on haplotype data for each population, haplotype diversity, and genetic distance.